Efeitos de polinizações mistas em espécies autoincompatíveis de Bignoniaceae - Duarte, Mariana Oliveira (2014)
The angiosperms have different strategies to prevent self-fertilization, either by pre- pollination mechanisms (herkogamy and dichogamy) or mechanisms for post-pollination (system of self-incompatibility and inbreeding depression). Some species present late-acting self-incompatibility (LSI), which can act after penetration or fertilization the ovule, causing abscission of selfed pistil. However, some studies on species with LSI reported the formation of seeds derived from selfing after mixed pollinations (pollen crossed + self-pollen). In the present work we investigated the possibility of formation of fruits and viable selfed seeds from mixed pollinations in three species of Bignoniaceae with LSI, Adenocalymma peregrinum, Fridericia platyphylla and Tabebuia aurea. We performed experimental pollination, germination of seeds (A. peregrinum), histological analysis of post- pollination events and paternity testing (T. aurea). The three species formed fruit after mixed pollination and cross-pollination, however, showed a lower rate of fruiting in mixed pollinations. The selfed pistils were aborted in a uniform period of time in all species, confirming the presence of the LSI. In A. peregrinum there was a greater percentage of seeds without embryo on fruit from mixed pollination. The lower germination of seeds of fruits mixed pollination of this species may indicate less ability to germinate seed from selfing and a possible role of inbreeding depression. The low rate of natural fruiting species with LSI can be explained by a high frequency the seeds resulting of self-fertilization after mixed pollinations, which should be common in the natural environment. Analysis of endosperm development in T. aurea showed a delay in the initial development of this tissue into ovules of selfed pistils compared to the ovules of pistils from cross-pollination, evidence of the action of LSI. Most ovules from pistils after mixed pollination showed a number of endosperm cells similar to the ovules of pistils submitted cross-pollination and no seeds originated from selfing were detected in paternity testing. Although paternity tests have detected the presence of selfing progeny in some species populations of Bignoniaceae and fruits formation of mixed pollinations has proved viable in the present study, our data showed that seeds from selfing did not seem to be formed or were less viable during germination and emergence.